2003
DOI: 10.1161/01.cir.0000087656.10829.df
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Coronary Revascularization, With and Without Mitral Valve Surgery, in Patients With Ischemic Mitral Regurgitation

Abstract: Background— The most appropriate treatment for patients with ischemic mitral regurgitation (IMR) is often debated. We compared the survival rates of patients with IMR undergoing different treatment strategies, namely: medical therapy, percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG), and CABG + mitral valve (MV) surgery. Methods and Results— Patients undergoing catheterization betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 31 publications
3
120
0
3
Order By: Relevance
“…16 Alternatively, MV repair may primarily affect other important end points, such as heart failure and adverse remodeling of the LV. 8,17 Our findings agree with the results of previous studies showing that percutaneous and surgical revascularization had comparable long-term survival 4,10 and that MV repair was insufficient to improve long-term survival. 6,7,18 However, to our knowledge, the present study is the first prospective study to demonstrate that compared with revascularization alone, additional mitral annuloplasty significantly improved functional status and long-term event-free survival by decreasing the incidence of persistent and recurrent IMR to 6%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…16 Alternatively, MV repair may primarily affect other important end points, such as heart failure and adverse remodeling of the LV. 8,17 Our findings agree with the results of previous studies showing that percutaneous and surgical revascularization had comparable long-term survival 4,10 and that MV repair was insufficient to improve long-term survival. 6,7,18 However, to our knowledge, the present study is the first prospective study to demonstrate that compared with revascularization alone, additional mitral annuloplasty significantly improved functional status and long-term event-free survival by decreasing the incidence of persistent and recurrent IMR to 6%.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] Percutaneous or surgical revascularization has been associated with improved survival compared with medical therapy in patients with IMR, 3,4 but the proper way of revascularization remains controversial. Surgical revascularization has potential benefits of achieving more complete revascularization and improving IMR more effectively by addition of a mitral valve (MV) procedure at the time of coronary artery bypass graft (CABG) surgery.…”
mentioning
confidence: 99%
“…1,5,7,8,16 Because severe IMR is not usually improved by revascularization alone, [17][18][19] current expert consensus 7,8 recommends concomitant restrictive annuloplasty at the time of CABG. On the other hand, in patients with moderate IMR undergoing CABG, the indication for concomitant mitral valve repair is highly controversial.…”
Section: Surgical Management Of Imrmentioning
confidence: 99%
“…However, in these patients, several recent studies have failed to demonstrate a long-term survival benefit of the combined procedure compared with CABG alone. [3][4][5]17,21 These surprising findings may be attributed partly to the high recurrence rate of IMR despite initially successful repair and higher perioperative mortality of the combined procedures compared with CABG alone. 2,13,17,19,[22][23][24] Furthermore, some studies have shown significant improvement in moderate IMR with CABG alone.…”
Section: Surgical Management Of Imrmentioning
confidence: 99%
“…Consistent with this analysis are the recent observations that MV repair for ischemic mitral regurgitation fails to provide any survival advantage. [15][16][17][18][19] This lack of benefit may be explained by the fact that up to 30% of patients develop recurrent mitral regurgitation after annuloplasty and coronary artery bypass graft surgery. The limited benefit of the conventional approach has stimulated the development and testing of new methods to more directly address the complex cause of the mitral regurgitation in these patients.…”
Section: Editorial See P 2755 Clinical Perspective On P 2843mentioning
confidence: 99%